FORMS OF LOCAL WISDOM IN THE SPEECH DISCOURSE OF THE PUGER FISHERMEN COMMUNITY, JEMBER - Fuad, Akhmad Dzukaul; Santoso, Anang; Pratiwi, Yuni; Roekhan, Roekhan; Thampu, Sainee (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2025)
The Puger fisherman in Jember, East Java Province, Indonesia, represents the local community on the south beach of East Java. The open attitude of the Puger fisherman forms unique communication characteristics and is supported by the pendalungan culture, i.e., a melting pot between the Javanese and Madurese cultures. This socio-cultural configuration positions the Puger fishermen as a multilingual and multicultural speech community whose communication practices are shaped by continuous cultural contact and adaptation. This allows communication events to be interpreted beyond the linguistic aspect, as they can be interpreted as a discourse of local wisdom that is full of meaning and values, which had so far escaped the attention of many researchers. In this sense, communication is not merely a medium for transmitting information but functions as a cultural practice that embodies social norms, identity construction, and collective knowledge. This article describes the communication wisdom of the Puger fisherman, which describes the form and value system in communication among them. The authors employed ethnographic communication methods based on speech obtained through observation and direct involvement in the communication events. This process produced recorded data, which was then reduced into speech data representing wisdom in communication. The results of data reduction were then analyzed using SPEAKING, which resulted in the classification of speech based on domain, theme, and socio-cultural aspects, which were present in the communication event. From this classification system, the authors can find the local wisdom of the Puger fishermen in their communication. The analytical focus on Hymes’ SPEAKING framework enables a comprehensive interpretation of communication as situated action shaped by setting, participants, purposes, norms, and genres. The communication wisdom of the Puger fisherman was represented by their lingual aspects and value systems. Lingual aspects were represented in their straightforward structure and diction, choice of language variations, and communication patterns. Meanwhile, local wisdom at the value system level was represented in language impressions; prohibitions on njangkar, njambal, and mapas; as well as intonation and gestures in communication. These features demonstrate how linguistic choices and communicative behavior are systematically governed by culturally embedded principles of respect, hierarchy, solidarity, and social harmony. The fishermen community’s communication patterns form wisdom in the discourse structure, contributing to how they plan their decisions and communicate their strategies to prevent social vulnerability and manage conflicts.